Flourensia cernua: Hexane Extracts a Very Active Mycobactericidal Fraction from an Inactive Leaf Decoction against Pansensitive and Panresistant Mycobacterium tuberculosis - Molina Salinas, Gloria María; Peña Rodríguez, Luis Manuel; Mata Cárdenas, Benito David; Escalante Erosa, Fabiola; González Hernández, Silvia; Torres de la Cruz, Víctor Manuel; Martínez Rodríguez, Herminia Guadalupe; Said Fernández, Salvador (2011)
The efficacy of decoction in extracting mycobactericidal compounds from Flourensia cernua (Hojas´e) leaves and fractionation with solvents having ascending polarity was compared with that of (i) ethanol extraction by still maceration, extraction with a Soxhlet device, shake-assisted maceration, or ultrasound-assisted maceration, followed by fractionation with n-hexane, ethyl acetate, and n-butanol; (ii) sequential extraction with n-hexane, ethyl acetate, and n-butanol, by still maceration, using a Soxhlet device, shake-assisted maceration, or ultrasound-assisted maceration. The in vitro mycobactericidal activity of each preparation was measured against drug-sensitive (SMtb) and drug-resistant (RMtb) Mycobacterium tuberculosis strains. The results of which were expressed as absolute mycobactericidal activity (AMA). These data were normalized to the ΣAMA of the decoction fraction set. Although decoction was inactive, the anti-RMtb normalized ΣAMA (NAMA) of its fractions was comparable with the anti-RMtb NAMA of the still maceration extracts and significantly higher than the anti-SMtb and anti-RMtb NAMAs of every other ethanol extract and serial extract and fraction. Hexane extracted, from decoction, material having 55.17% and 92.62% of antituberculosis activity against SMtb and RMtb, respectively. Although the mycobactericidal activity of decoction is undetectable; its efficacy in extracting F. cernua active metabolites against M. tuberculosis is substantially greater than almost all pharmacognostic methods.